Descriptores para Camu Camu Myrciaria dubia (Kunth) Mc Vaugh - Imán Correa, Sixto Alfredo; Chuquizuta del Castillo, Badys; Samanamud Curto, Angelo Francisco; Ochoa Vásquez, Marjorie (Instituto Nacional de Innovación Agraria, 2022)
34 páginas